On Language and Thought: Bilingual Experience Influences Semantic Associations - Ning, Siqi (J Neurolinguistics, 2020)
Language can influence cognition in domains as varied as temporal processing, spatial categorization, and color perception (Casasanto & Boroditsky, 2008; Levinson & Wilkins, 2006; Winawer et al., 2007). Here, we provide converging behavioral and neural evidence that bilingual experience can change semantic associations. In Experiment 1, Spanish- and English-speaking bilinguals rated semantically unrelated picture pairs (e.g., cloud-present) as significantly more related in meaning than English monolinguals. Experiment 2 demonstrated that bilinguals who were highly proficient in Spanish and English rated both semantically related (e.g., student-teacher) and unrelated picture pairs (e.g., wall-fruit) as more related than monolinguals and low-proficiency bilinguals. Experiment 3 added ERP measures to provide a more sensitive test of the bilingual effect on semantic ratings, which was assessed through the use of linguistic stimuli (related and unrelated words instead of pictures) and a different bilingual population (Korean-English bilinguals). Bilingualism was associated with a significantly smaller N400 effect (i.e., N400 for unrelated - related), suggesting that bilinguals processed related and unrelated pairs more similarly than monolinguals; this result was coupled with a non-significant behavioral trend of bilinguals judging unrelated words as more related than monolinguals did. Across the three experiments, results show that bilingual experience can influence perceived semantic associations. We propose that bilinguals’ denser and more interconnected phonological, orthographic and lexical systems may change the links between semantic concepts. Such an account is consistent with connectionist models of language that allow for phonological and lexical influences on conceptual representations, with implications for models of bilingual language processing.